The management skills of academic head librarians in Quezon City - Tampoc, Leoghenes A. (School of Library and Information Studies, University of the Philippines Diliman, 2002)
The research paper focused on the level of management skill of the academic head librarians in Quezon City. Also, this research was concerned with the educational attainment and length of work experience of these academic head librarians. The researcher aimed to determine whether these academic head librarians have a low or high management skill and whether their educational attainment and length of work experience is related to their level of management skill.